Alfalfa Cost-Return Budget in North Central and Northeast Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2001)
This publication contains information for a projected budged reflecting expected income and cost based on typical alfalfa production practices in the central and northeast region of Kansas.
MF2365_2001_10
Keywords: MF2365; Economics; Crops; MF